Bile metabolites of polycyclic aromatic hydrocarbons (PAHs) as a biomarker of pollution in European eel (Anguilla anguilla) from German rivers ... - Nagel, F.; Kammann, U.; Hanel, R. (ASC 2010 - Theme session F, 2024)
No abstracts are to be cited without prior reference to the author.Polycyclic aromatic hydrocarbons (PAHs) and their metabolites are important environmental contaminants that may lead to increased levels of neoplastic aberrations or tumours in fish liver. Therefore, PAHs and their metabolites in fish bile can be used as biomarkers of PAH exposure in the aquatic environment. The aim of the present study was to examine PAH metabolites in the bile of European eel (Anguilla anguilla) from 12 rivers in Germany to investigate the concentrations of PAH metabolites and to elucidate spatial differences. In total, 180 yellow eels (15 eels per river) were collected at downstream sites of the rivers Rhine, Elbe, Havel, Oder, Uecker, Weser, Ems, Schlei, Trave, Eider, Warnow, and Peene in 2009. The deconjugated PAH metabolites in the eel bile were analysed using HPLC with fluorescence detection and normalized to bile pigments. Three PAH metabolites were quantified: metabolites of pyrene, phenanthrene, and benzopyrene. ...